High-uniformity nanofiltration membrane for purifying pilose antler peptide
By regulating the ratio of spinning liquid and performing hydrophilic modification, combined with ultrasonic treatment and nanoparticle addition, a composite nanofiltration membrane with high uniformity and mechanical strength was prepared, which solved the problem of fractionation and separation of amino acids, oligopeptides and peptides in the deer antler hydrolysate, and achieved accurate separation and product quality improvement.
Patent Information
- Application Number
- CN202411759938.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The prior art is difficult to efficiently and accurately separate amino acids, oligopeptides and polypeptides in deer antler hydrolysates, and the pore size and thickness uniformity of traditional membrane materials is insufficient and cannot adapt to environmental changes.
The polyacrylonitrile membrane is hydrophilicly modified by regulating the spinning liquid ratio and alkaline solution, and the dispersion of the polyacrylonitrile solution is optimized through ultrasonic treatment, titanium dioxide nanoparticles and surfactant are added, and a composite nanofiltration membrane with higher uniformity and mechanical strength is prepared in combination with electrospinning technology.
Accurate separation of antler peptides of different molecular weights is achieved, separation accuracy and film uniformity are improved, the shortcomings of traditional film materials are overcome, and product quality and processing efficiency are enhanced.
Abstract
Description
Technical Field
[0001] The invention relates to the field of membrane science and technology, and in particular to a method for preparing a composite nanofiltration membrane for efficiently and accurately separating amino acids, oligopeptides and polypeptides from velvet antler hydrolysates. Background Art
[0002] Amino acids are the basic units that make up proteins, containing amino and carboxyl groups. Among them, oligopeptides are composed of 2-20 amino acids connected by peptide bonds, while polypeptides are composed of more amino acids. Amino acids form peptide bonds through dehydration condensation reactions, connect into dipeptides, and then gradually form oligopeptides and polypeptides. Structurally, oligopeptides and polypeptides are based on amino acids, and peptide bonds connect each amino acid. In terms of function, amino acids are involved in metabolic regulation, oligopeptides can be used as signaling molecules, etc., while polypeptides play more complex functions, such as insulin regulating blood sugar. They are closely connected, from amino acids to oligopeptides to polypeptides, the structure gradually becomes complex, and the function continues to expand.
[0003] Deer antler peptide is a bioactive substance extracted from deer antler and is one of the important effective ingredients in deer antler. Deer antler peptide is usually a small molecule peptide composed of multiple amino acids, which has a variety of physiological activities, such as enhancing immunity, promoting tissue repair and regeneration, and contributing to bone health. In view of the unique efficacy of deer antler peptide, it has broad application prospects in the fields of medicine and health care products. At present, the preparation methods of deer antler peptide mainly include enzymatic hydrolysis and lysis liquid method, among which enzymatic hydrolysis is one of the commonly used methods. In view of the different sizes of peptides in deer antler hydrolysate, it contains oligopeptides (oligopeptides) and polypeptides, whose molecular weights are between 180-1000 Daltons and 1000-5000 Daltons, respectively. These peptide molecules may be composed of 2-10 amino acids and 10-50 amino acids. Factors such as the type of enzyme selected in the deer antler hydrolysis process, enzymatic hydrolysis time and temperature play an important role in the size of the peptide. The membrane separation method for preparing deer antler peptide has high separation accuracy and mild separation conditions, which helps to improve product quality and medicinal value, and can retain the active ingredients of deer antler peptide to the greatest extent.
[0004] The core technology of the present invention is to purify antler peptides using a nanofiltration membrane with high uniformity, thereby achieving accurate separation of antler peptides of different molecular weights. By re-dissolving the nanofiber membrane after spinning and forming the membrane again, the pore size of the membrane can be made more uniform and accurate, and the thickness of the membrane can be controlled more accurately. The advantage of this technological innovation is that it improves the separation accuracy of antler peptides, enhances the uniformity of the membrane, and overcomes the shortcomings of traditional membrane materials that the pore size and thickness are not uniform and cannot adapt to environmental changes. It is expected to cause major changes in the field of antler peptide production, improve product quality and processing efficiency, expand the application range of antler peptides, and have broad market prospects and economic benefits. Summary of the invention
[0005] In view of the complex problem of fractional separation of amino acids, oligopeptides and polypeptides, the present invention provides a method for preparing a hydrophilic nanofiltration composite membrane for fractional separation of amino acids, oligopeptides and polypeptides. It is characterized in that the polyacrylonitrile membrane is hydrophilically modified by regulating the spinning solution ratio and alkaline solution, and the dispersibility of the polyacrylonitrile solution is optimized by ultrasonic treatment to make it better dissolve functional particles, and a surfactant is added to reduce the surface tension of the solution, and then the re-dissolved nanofiber membrane solution is spun. The obtained polyacrylonitrile membrane has higher structural uniformity and mechanical strength, and the physical properties of the membrane are enhanced. The polyacrylonitrile electrospinning membrane containing titanium dioxide nanoparticles can be used to prepare antibacterial materials, such as medical supplies, food packaging materials, etc., to reduce bacterial growth, which also improves its ability to resist environmental influences, making it more suitable for demanding application environments. In addition, the hydrophilic and antifouling properties of the polyacrylonitrile membrane are improved, the water flux is more controllable, and a good retention rate for polypeptides is retained.
[0006] The object of the present invention is to provide a method for preparing a composite nanofiltration membrane for fractional separation of amino acids, oligopeptides and polypeptides.
[0007] 1. The composite nanofiltration membrane preparation method of the present invention comprises the following key steps: Add polyacrylonitrile powder to one or more organic solvents, heat and stir until completely dissolved to form polyacrylonitrile solution A; use electrospinning technology to make polyacrylonitrile solution A into nanofiber membrane to form a uniform nanofiber network structure; add NaOH to modify the prepared nanofiber membrane to neutralize the acidic groups on the membrane surface. Dissolve the modified polyacrylonitrile membrane, and treat the dissolved solution with ultrasound; add titanium dioxide nanoparticles to the polyacrylonitrile solution A after ultrasound treatment, and add surfactant sodium dodecyl sulfate (SDS) and stir well to form polyacrylonitrile solution B; and use electrospinning technology to make a membrane of polyacrylonitrile solution B; dry the membrane under constant temperature to obtain a preliminarily formed polyacrylonitrile membrane; pour PIP aqueous solution and TMC n-hexane solution on the membrane for interfacial polymerization reaction. Wash the polyacrylonitrile membrane after the interfacial treatment to remove the residual reagents, and dry it to obtain the final composite nanofiltration membrane.
[0008] 2. As a further preferred embodiment of the present invention, the ratio of polyacrylonitrile powder to organic solvent is 8-12wt%; the organic solvent is one or more of DMF, DMAc, methanol or butanol; the stirring time is 20-30 minutes, the heating temperature is 80-90°C, the stirring speed is 300-500rpm, the stirring time is 2-3 hours, the formed polyacrylonitrile solution A is cooled to room temperature, and stirring is continued for 10-15 minutes.
[0009] 3. As a further preferred embodiment of the present invention, the mixed solution is loaded into a syringe, the needle diameter of the syringe is selected to be 0.2-0.5 mm; the spinning voltage is 15-25 kV; the injection rate is 0.5-1.5 mL / h, and the spinning distance is 10-20 cm; 4. As a further preferred embodiment of the present invention, the NaOH alkaline solution is 1 mol / L, the stirring time is 2 h, and the temperature is 60°C; 5. As a further preferred embodiment of the present invention, the ratio of the modified nanofiber membrane to the organic solvent is 10-15wt%; the heating temperature is 80-90°C, the stirring speed is 300-500rpm, the stirring time is 1-2 hours, and the stirring time is 10-15 minutes after cooling to room temperature; 6. As a further preferred embodiment of the present invention, the dissolved polyacrylonitrile solution B is placed in a container of an ultrasonic treatment device to ensure that the liquid level of the solution does not exceed two-thirds of the container; the frequency of the ultrasonic treatment device is 20-40kHz, and the power is 200-400 watts; the treatment time is 10-20 minutes; during the treatment process, the solution temperature is maintained at 30-40°C; the stirring speed of the magnetic stirrer is set to 200-400 rpm, and the initial stirring time is 10-15 minutes; the mixed solution is transferred to a high-speed stirring device, the stirring speed is adjusted to 1000-1500 rpm, and the stirring is continued for 30-45 minutes. After the stirring is completed, the mixed solution is allowed to stand for 5-10 minutes; 7. As a further preferred embodiment of the present invention, the titanium dioxide nanoparticles are added in an amount of 0.5-1 wt %; the SDS is added in an amount of 1-2 wt %; 8. As a further preferred embodiment of the present invention, the temperature of the constant temperature drying oven is set at 45-55°C; and the drying time is 10-15 minutes.
[0010] 9. As a further preferred embodiment of the present invention, the mass concentration of the PIP solution is 0.025-0.125 wt %, and the soaking time of the polyacrylonitrile nanofiber membrane is 2-3 minutes.
[0011] 10. As a further preferred embodiment of the present invention, the mass fraction of the TMC n-hexane solution added dropwise is 0.1-0.2 wt%, including the dropwise addition of 2 mL of 0.1 wt% TMC, and the interfacial polymerization time is 20-60 seconds.
[0012] 11. As a further preferred embodiment of the present invention, the composite nanofiltration membrane is rinsed with deionized water for 3 to 4 times, and then soaked for 12 to 15 hours to remove the residual reagents. The membrane is dried at room temperature for more than 12 hours to finally obtain the final composite nanofiltration membrane.
[0013] The invention provides a method for preparing a hydrophilic composite nanofiltration membrane for separating polypeptides from amino acids and oligopeptides. The polypeptide retention rate of the composite nanofiltration membrane is greater than 95%.
[0014] 1. The beneficial effect of this patent is that it combines ultrasonic treatment, the addition of nanoparticles and surfactants, and electrospinning technology to significantly improve the uniformity and anti-pollution performance of polyacrylonitrile membranes. This innovative technology not only enhances the bonding force between the separation layer and the base membrane, but also improves the integrity of the separation layer, improves the performance stability of the separation layer, and optimizes the microstructure of the separation layer.
[0015] 2. By dissolving the spun nanofiber membrane, the polyacrylonitrile molecules constituting the membrane are evenly dispersed in the solvent, and by adjusting the film-forming conditions during the re-filming process, these molecules are rearranged and distributed, avoiding local aggregation or uneven distribution, eliminating the original defects and unevenness, and making the thickness of the final membrane more accurately controlled. Under suitable temperature and concentration conditions, the disordered state is transformed into an ordered membrane phase, making the formed membrane more uniform, enhancing the bonding force between the separation layer and the base membrane, and improving its ability to resist environmental influences, making it more suitable for harsh application environments.
[0016] This method has relatively low implementation cost, simple process, and is suitable for large-scale industrial production. It provides a new, more efficient, economical and environmentally friendly way for the preparation of polyacrylonitrile membranes, and has high practical value and broad market potential. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is further described below in conjunction with specific embodiments. These embodiments should not be construed as limiting the technical solution. Example
[0018] 8g of polyacrylonitrile powder was added to 100 mL of DMF organic solvent, stirred at 85°C at 400rpm for 2.5 hours to form polyacrylonitrile solution A, then cooled to room temperature and continued to stir for 12 minutes. Polyacrylonitrile solution A was loaded into a syringe with a needle diameter of 0.3mm, and a nanofiber membrane was made by electrospinning technology at a spinning voltage of 20kV, an injection rate of 1mL / h and a spinning distance of 15cm. Then, the nanofiber membrane was placed in a 1mol / L NaOH alkaline solution and stirred at 60°C for 2 hours for modification. The modified nanofiber membrane was redissolved in DMF at a ratio of 12wt%, stirred at 85°C and 400 rpm for 1.5 hours, cooled to room temperature and stirred for another 12 minutes. The dissolved solution was placed in an ultrasonic treatment device (frequency 30kHz, power 300 watts), treated at 35°C for 15 minutes, and initially stirred at 300rpm for 12 minutes with a magnetic stirrer, then transferred to a high-speed stirring device and stirred at 1200 rpm for 40 minutes, and then allowed to stand for 8 minutes to obtain a treated polyacrylonitrile solution A. 0.8wt% of titanium dioxide nanoparticles and 1.5wt% of SDS were added to the solution and stirred thoroughly to form a polyacrylonitrile solution B, which was then formed by electrospinning technology and dried in a constant temperature drying oven at 50°C for 12 minutes to obtain a preliminarily formed polyacrylonitrile membrane. The membrane was infiltrated with a PIP aqueous solution with a mass concentration of 0.05wt% for 2.5 minutes, and then 2 mL of a TMC n-hexane solution with a mass fraction of 0.15wt% was added dropwise, the interfacial polymerization time was 40s, and finally rinsed with deionized water 3 times, soaked for 13 hours to remove residual reagents, and dried at room temperature for 13 hours to obtain a composite nanofiltration membrane.
[0019] Pore size uniformity: The pore size distribution of the membrane was measured by mercury intrusion porosimetry. The coefficient of variation of the pore size was 9%, and the ratio of the maximum pore size to the minimum pore size was 1.35.
[0020] Thickness uniformity: measured by laser interferometry, the film surface is divided into 1cm×1cm squares, 100 points are measured, the thickness deviation rate is ±3.5%, and the thickness standard deviation is 6 nm.
[0021] Purification effect of antler peptides: The antler peptides with a molecular weight of more than 1000 Da were separated with a separation efficiency of 90%, a yield of 85%, and a flux of 50 L / (m²・h). Example
[0022] 8g of polyacrylonitrile powder was added to 100mL of DMF organic solvent, stirred at 300rpm for 3 hours at 80℃ to form polyacrylonitrile solution A, cooled to room temperature and continued to stir for 15 minutes. The mixed solution was placed in an ultrasonic treatment device (frequency 20kHz, power 200 watts), treated at 30℃ for 20 minutes, and initially stirred at 200 rpm for 15 minutes with a magnetic stirrer, then transferred to a high-speed stirring device and stirred at 1000 rpm for 45 minutes, and allowed to stand for 10 minutes to obtain the treated polyacrylonitrile solution A. 0.5wt% of titanium dioxide nanoparticles and 1wt% of SDS were added to the solution and stirred thoroughly to form polyacrylonitrile solution B, which was then formed into a membrane by electrospinning technology and dried in a constant temperature drying oven at 45℃ for 15 minutes to obtain a preliminarily formed polyacrylonitrile membrane. The membrane was soaked in a 0.025wt% PIP aqueous solution for 3 minutes, and then 2mL of a 0.1wt% TMC n-hexane solution was added dropwise. The interfacial polymerization time was 60 seconds. Finally, it was rinsed with deionized water for 4 times, soaked for 15 hours to remove residual reagents, and dried at room temperature for 15 hours to obtain the final composite nanofiltration membrane.
[0023] Pore size uniformity: measured by mercury intrusion porosimetry, the coefficient of variation of pore size is 20%, and the ratio of maximum pore size to minimum pore size is 1.9.
[0024] Thickness uniformity: 100 points were measured according to the above grid by laser interferometry, the thickness deviation rate was ±9%, and the thickness standard deviation was 15 nm.
[0025] Purification effect of antler peptides: For the separation of antler peptides with a molecular weight of more than 1800 Da, the separation efficiency is 88%, the yield is 82%, and the flux is 35 L / (m²・h). Example
[0026] 8g of polyacrylonitrile powder was added to 80mL of methanol organic solvent, stirred at 90℃ for 2 hours at 500 rpm to form polyacrylonitrile solution A, cooled to room temperature and continued to stir for 10 minutes. Polyacrylonitrile solution A was loaded into a syringe with a needle diameter of 0.5mm, and a nanofiber membrane was made by electrospinning technology at a spinning voltage of 25kV, an injection rate of 1.5mL / h and a spinning distance of 20cm. After that, the nanofiber membrane was placed in a 1mol / L NaOH alkaline solution and stirred at 60℃ for 2 hours for modification. The modified nanofiber membrane was redissolved in methanol at a ratio of 15wt%, stirred at 90℃ and 500 rpm for 1 hour, cooled to room temperature and stirred for another 10 minutes. The dissolved solution was placed in an ultrasonic treatment device (frequency 40 kHz, power 400 watts), treated at 40°C for 10 minutes, and initially stirred at 400 rpm for 10 minutes with a magnetic stirrer, then transferred to a high-speed stirring device and stirred at 1500 rpm for 30 minutes, and then allowed to stand for 5 minutes to obtain a treated polyacrylonitrile solution A. 1wt% of titanium dioxide nanoparticles and 2wt% of SDS were added to the solution and stirred thoroughly to form a polyacrylonitrile solution B, which was then formed by electrospinning technology and dried in a constant temperature drying oven at 55°C for 10 minutes to obtain a preliminarily formed polyacrylonitrile membrane. The membrane was infiltrated with a PIP aqueous solution with a mass concentration of 0.125wt% for 2min, and then 2mL of a TMC n-hexane solution with a mass fraction of 0.2wt% was added dropwise, the interfacial polymerization time was 20s, and finally rinsed with deionized water 3 times, soaked for 12 hours to remove residual reagents, and dried at room temperature for 12 hours to obtain the final composite nanofiltration membrane.
[0027] Pore size uniformity: The coefficient of variation of pore size measured by mercury intrusion porosimetry was 8%, and the ratio of the maximum pore size to the minimum pore size was 1.3.
[0028] Thickness uniformity: Using laser interferometry, 100 points are measured on a grid, the thickness deviation rate is ±3%, and the thickness standard deviation is 5nm.
[0029] Purification effect of antler peptides: For the separation of antler peptides with a molecular weight of more than 800Da, the separation efficiency is 92%, the yield is 88%, and the flux is 55L / (m²・h). Example
[0030] 9 g of polyacrylonitrile powder was added to 110 mL of butanol organic solvent, stirred at 82 °C at 350 rpm for 2.8 hours to form polyacrylonitrile solution A, cooled to room temperature and continued to stir for 13 minutes. Polyacrylonitrile solution A was loaded into a syringe with a needle diameter of 0.4 mm, and a nanofiber membrane was prepared by electrospinning technology at a spinning voltage of 18 kV, an injection rate of 1.2 mL / h and a spinning distance of 18 cm. Subsequently, the nanofiber membrane was placed in a 1 mol / L NaOH alkaline solution and stirred at 60 °C for 2 hours for modification. The modified nanofiber membrane was redissolved in butanol at a ratio of 13 wt%, stirred at 82 °C and 350 rpm for 1.8 hours, cooled to room temperature and stirred for another 13 minutes. The dissolved solution was placed in an ultrasonic treatment device (frequency 35 kHz, power 350 watts) and treated at 38°C for 18 minutes. At the same time, it was initially stirred at 350 rpm for 13 minutes with a magnetic stirrer, and then transferred to a high-speed stirring device and stirred at 1300 rpm for 35 minutes. It was allowed to stand for 7 minutes to obtain the treated polyacrylonitrile solution A. 0.6wt% of titanium dioxide nanoparticles and 1.8wt% of SDS were added to the solution and stirred thoroughly to form polyacrylonitrile solution B, which was then formed into a membrane by electrospinning technology and dried in a constant temperature drying oven at 52°C for 13 minutes to obtain a preliminarily formed polyacrylonitrile membrane. The membrane was soaked in a 0.08wt% PIP aqueous solution for 2.8min, and then 2mL of a 0.18wt% TMC n-hexane solution was added dropwise. The interfacial polymerization time was 50s. Finally, it was rinsed with deionized water for 3 times, soaked for 14 hours to remove residual reagents, and dried at room temperature for 14 hours to obtain the final composite nanofiltration membrane.
[0031] Pore size uniformity: measured by mercury intrusion porosimetry, the coefficient of variation of pore size is 9.5%, and the ratio of the maximum pore size to the minimum pore size is 1.38.
[0032] Thickness uniformity: By laser interferometry, 100 points were measured on a grid, the thickness deviation rate was ±3.8%, and the thickness standard deviation was 6.5 nm.
[0033] Purification effect of antler peptides: The antler peptides with a molecular weight of more than 1100 Da were separated with a separation efficiency of 89%, a yield of 86%, and a flux of 48 L / (m²・h). Example
[0034] 11 g of polyacrylonitrile powder was added to 90 mL of mixed organic solvent (DMF and methanol volume ratio 1:1), stirred at 88 ° C at 450 rpm for 2.2 hours to form polyacrylonitrile solution A, cooled to room temperature and continued to stir for 11 minutes. Polyacrylonitrile solution A was loaded into a syringe with a needle diameter of 0.35 mm, and a nanofiber membrane was prepared by electrospinning technology at a spinning voltage of 22 kV, an injection rate of 0.8 mL / h and a spinning distance of 12 cm. Then, the nanofiber membrane was placed in a 1 mol / L NaOH alkaline solution and stirred at 60 ° C for 2 hours for modification. The modified nanofiber membrane was redissolved in a mixed organic solvent at a ratio of 14wt%, stirred at 88 ° C and 450 rpm for 1.2 hours, cooled to room temperature and stirred for another 11 minutes. The dissolved solution was placed in an ultrasonic treatment device (frequency 32 kHz, power 320 watts) and treated at 32°C for 16 minutes. At the same time, it was initially stirred at 320 rpm for 11 minutes with a magnetic stirrer, and then transferred to a high-speed stirring device and stirred at 1400 rpm for 32 minutes. It was allowed to stand for 6 minutes to obtain the treated polyacrylonitrile solution A. 0.9wt% of titanium dioxide nanoparticles and 1.6wt% of SDS were added to the solution and stirred thoroughly to form a polyacrylonitrile solution B, which was then formed into a membrane by electrospinning technology and dried in a constant temperature drying oven at 53°C for 11 minutes to obtain a preliminarily formed polyacrylonitrile membrane. The membrane was soaked in a 0.1wt% PIP aqueous solution for 2.2min, and then 2mL of a 0.16wt% TMC n-hexane solution was added dropwise. The interfacial polymerization time was 30s. Finally, it was rinsed with deionized water for 4 times, soaked for 13.5 hours to remove residual reagents, and dried at room temperature for 13.5 hours to obtain the final composite nanofiltration membrane.
[0035] Pore size uniformity: The coefficient of variation of pore size measured by mercury intrusion porosimetry was 8.5%, and the ratio of the maximum pore size to the minimum pore size was 1.32.
[0036] Thickness uniformity: Using laser interferometry, 100 points were measured on a grid, the thickness deviation rate was ±3.2%, and the thickness standard deviation was 5.5 nm.
[0037] Purification effect of antler peptides: For the separation of antler peptides with a molecular weight of more than 900 Da, the separation efficiency is 91%, the yield is 87%, and the flux is 52 L / (m²・h).
Claims
1. A method for preparing a nanofiltration membrane for fractionation of amino acids, oligopeptides and polypeptides, characterized in that The following steps are involved: Add polyacrylonitrile powder to one or more organic solvents, heat and stir until completely dissolved, to form polyacrylonitrile solution A; The polyacrylonitrile solution A is made into a nanofiber membrane by electrospinning technology to form a uniform nanofiber network structure; after the nanofiber membrane is made, NaOH is added to modify it to neutralize the acidic groups on the membrane surface. The modified polyacrylonitrile membrane is dissolved, and the dissolved solution is subjected to ultrasonic treatment; titanium dioxide nanoparticles are added to the polyacrylonitrile solution A after ultrasonic treatment, and a surfactant, sodium dodecyl sulfate, is added and fully stirred to form a polyacrylonitrile solution B; the polyacrylonitrile solution B is subjected to electrospinning to form a membrane; the membrane is dried under constant temperature conditions to obtain a preliminarily formed polyacrylonitrile membrane; PIP aqueous solution and TMC n-hexane solution were poured onto the membrane for interfacial polymerization reaction. The polyacrylonitrile membrane after the interface treatment was washed to remove the residual reagents and dried to obtain the final composite nanofiltration membrane.
2. A method for preparing a nanofiltration membrane for fractionation and separation of amino acids, oligopeptides and polypeptides as claimed in claim 1, characterized in that: The ratio of polyacrylonitrile powder to organic solvent is 8-12wt%; the organic solvent is one or more of DMF, DMAc, methanol or butanol; the stirring time is 20-30 minutes, the heating temperature is 80-90°C, the stirring speed is 300-500 rpm, the stirring time is 2-3 hours, the formed polyacrylonitrile solution A is cooled to room temperature, and stirring is continued for 10-15 minutes.
3. A method for preparing a nanofiltration membrane for fractionation and separation of amino acids, oligopeptides and polypeptides as claimed in claim 1, characterized in that: The mixed solution is loaded into a syringe, the needle diameter of the syringe is selected to be 0.2-0.5 mm; the spinning voltage is 15-25 kV; the injection rate is 0.5-1.5 mL / h, and the spinning distance is 10-20 cm; the NaOH alkaline solution is 1 mol / L, the stirring time is 2 h, and the temperature is 60°C.
4. A method for preparing a nanofiltration membrane for fractionation and separation of amino acids, oligopeptides and polypeptides as claimed in claim 1, characterized in that: The ratio of the modified nanofiber membrane to the organic solvent is 10-15wt%; the heating temperature is 80-90°C, the stirring speed is 300-500 rpm, the stirring time is 1-2 hours, and the stirring time is 10-15 minutes after cooling to room temperature.
5. A method for preparing a nanofiltration membrane for fractionation and separation of amino acids, oligopeptides and polypeptides as claimed in claim 1, characterized in that: The dissolved polyacrylonitrile solution B is placed in a container of an ultrasonic treatment device to ensure that the liquid level of the solution does not exceed two-thirds of the container; the frequency of the ultrasonic treatment device is 20-40 kHz, and the power is 200-400 watts; the treatment time is 10-20 minutes; during the treatment process, the solution temperature is maintained at 30-40°C; the stirring speed of the magnetic stirrer is set to 200-400 rpm, and the initial stirring time is 10-15 minutes; the mixed solution is transferred to a high-speed stirring device, the stirring speed is adjusted to 1000-1500 rpm, and the stirring is continued for 30-45 minutes. After the stirring is completed, the mixed solution is allowed to stand for 5-10 minutes.
6. A method for preparing a nanofiltration membrane for fractionation of amino acids, oligopeptides and polypeptides as claimed in claim 1, characterized in that: The titanium dioxide nanoparticles are added in an amount of 0.5-1 wt %; and the SDS is added in an amount of 1-2 wt %.
7. A method for preparing a nanofiltration membrane for fractionation and separation of amino acids, oligopeptides and polypeptides as claimed in claim 1, characterized in that: The mass concentration of the PIP solution is 0.025wt% to 0.125wt% and the soaking time of the polyacrylonitrile nanofiber membrane is 2 to 3 minutes.
8. A method for preparing a nanofiltration membrane for fractionation and separation of amino acids, oligopeptides and polypeptides as claimed in claim 1, characterized in that: The mass fraction of the n-hexane solution of TMC added dropwise is 0.1-0.2 wt%, including adding 2 mL of 0.1 wt% TMC dropwise, and the interfacial polymerization time is 20-60 seconds.
9. A method for preparing a nanofiltration membrane for fractionation and separation of amino acids, oligopeptides and polypeptides as claimed in claim 1, characterized in that: The polyacrylonitrile is rinsed with deionized water for 3 to 4 times, and then soaked for about 12 to 15 hours to remove the residual reagent, and dried at room temperature for more than 12 hours.
Citation Information
Patent Citations
TiO2 / PSF (polysulfone) nanofiber forward osmosis composite membrane and preparation method thereof
CN106492637A
Method for preparing composite nanofiltration membrane through mixed solvent electrostatic spinning
CN117443213A
Metal oxide nanofibrous materials for photodegradation of environmental toxins
US20170056873A1